2014
DOI: 10.1089/scd.2014.0071
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Adipose-Derived Stromal Cells Without Enzymatic Treatment: Expansion, Phenotypical, and Functional Characterization

Abstract: Stem cell therapy is a potential method for the treatment of numerous diseases. The most frequent cellular source is bone-marrow-derived mesenchymal stromal cells (BM-MSCs). Human adipose-derived stromal cells (ADSCs) share similar properties with BM-MSCs as they support hematopoiesis, modulate ongoing immune responses, and differentiate into cells of mesodermal origin. On the other hand, ADSCs have higher frequency in situ, higher availability, and very few ethical issues compared with BM-MSCs, giving them an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 54 publications
0
44
0
1
Order By: Relevance
“…2B). These observations demonstrated that HBASCs resemble other ASCs in terms of their morphology and proliferation capacity [26,28]. The HBASCs displayed positive staining for the mesenchymal surface markers CD29, CD44, CD49d, CD73, CD90, CD105 and HLA-ABC/FITC, as determined through flow cytometry analysis ( Table 3).…”
Section: Characterization and Immunophenotype Of Hbascsmentioning
confidence: 75%
See 1 more Smart Citation
“…2B). These observations demonstrated that HBASCs resemble other ASCs in terms of their morphology and proliferation capacity [26,28]. The HBASCs displayed positive staining for the mesenchymal surface markers CD29, CD44, CD49d, CD73, CD90, CD105 and HLA-ABC/FITC, as determined through flow cytometry analysis ( Table 3).…”
Section: Characterization and Immunophenotype Of Hbascsmentioning
confidence: 75%
“…CD105, CD90 and CD44 are the three main positive markers used for MSCs, while CD34 is the most frequently reported negative marker. CD49d and CD31 have also been described as a positive marker and a negative marker, respectively [28].…”
Section: Characterization and Immunophenotype Of Hbascsmentioning
confidence: 99%
“…As was previously shown for the isolation of human adipose or Wharton jelly stem/progenitor cells, minimal manipulation leads to higher safety and efficacy of cell production (15,16). In this study, we selected exclusively impacted third molars between Nolla developmental stages 5 (crown almost completed) and 7 (one third root completed) to minimize the risk of pulp tissue contamination with oral microorganisms and to avoid the cell stress that results from crown root mechanical separation during the pulp recovery from older teeth (4,14).…”
Section: Discussionmentioning
confidence: 89%
“…We have chosen to deal with BM and AT as they represent the two main sources for MSC isolation in clinical trials [25]. AT seems to be an alternative source of MSC for cell-based therapy as some disadvantages are associated with BM [26,27] In our study, we demonstrated that MSC enrichment from a fresh sample was possible thanks to an appropriate cell selection. Importantly, the choice of the cell surface marker with which to proceed with the selection depended on the source of the sample as well as the therapeutical use of the MSC.…”
mentioning
confidence: 70%